2017
DOI: 10.1038/cmi.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

B7-DC (PD-L2) costimulation of CD4+ T-helper 1 response via RGMb

Abstract: The role of B7-DC in T-cell responses remains controversial because both coinhibitory and costimulatory functions have been reported in various experimental systems in vitro and in vivo. In addition to interacting with the coinhibitory receptor PD-1, B7-DC has also been shown to bind repulsive guidance molecule b (RGMb). The functional consequences of the B7-DC/RGMb interaction, however, remain unclear. More than a decade ago, we reported that replacement of a murine B7-DC mutant lysine with serine (K113S) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…8,13,32 Nevertheless, PD-L2 would be significantly upregulated by a series of cytokines which were stimulated by tumor microenvironment, such as IL-15 and IL-7. 9,13,33,34 In recent years, emerging data has shown that PD-L2 mainly focused on inducing the phase of T cell immunity and response in esophageal squamous cell carcinoma, 35 colorectal cancer, 36 and hepatocellular carcinoma. 37 However, the potential roles of PD-L2 in glioma were relatively less studied than PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…8,13,32 Nevertheless, PD-L2 would be significantly upregulated by a series of cytokines which were stimulated by tumor microenvironment, such as IL-15 and IL-7. 9,13,33,34 In recent years, emerging data has shown that PD-L2 mainly focused on inducing the phase of T cell immunity and response in esophageal squamous cell carcinoma, 35 colorectal cancer, 36 and hepatocellular carcinoma. 37 However, the potential roles of PD-L2 in glioma were relatively less studied than PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…Further work by Shin and colleagues demonstrated that PD-L2 inhibits Th2 responses induced by the nematode Nippostrongylus brasiliensis in a PD-1–independent manner (110). Thus, there is strong evidence for PD-L2 suppression of Th2 responses through PD-1–independent mechanisms (111). Indeed, the distinct phenotypes of PD-1 −/− mice (moderate increases in PC-specific IgM and total IgM levels) and PD-L2 −/− mice (significant increases in PC-specific IgM, significant decreases in total IgM levels) raise the question of whether PD-L2 regulation of PC-specific Ab secretion is also PD-1–independent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showing that targeting RGMb decreased lung inflammation is consistent with our findings. 34 Moreover, we showed that the RGMb 1 interstitial macrophages also played an important role because they expressed IL-17RB, the receptor for IL-25, which was required in our mouse model of allergen-driven AHR. An important role for IL-25 in human asthma has been demonstrated in clinical studies 35,36 and confirmed by human genetic studies.…”
Section: Discussionmentioning
confidence: 78%